Ammonia Volatilization from Different Soils Amended with Organic Materials - FORGHANI, AKBAR (Asian Journal of Chemistry, 2010)
A series of experiments were conducted on different soils (Alfisol, Vertisol and Entisol) under laboratory conditions to measure ammonia voltalization losses as affected by rate of organic matter (City Compost, FYM < glyricidia and pongamia litter) application. It has been observed that irrespective of type of organic matter applied, the maximum voltalization loss occured during first 2 weeks and gradually the rate of loss was lower and the loss was negligible after 18 d. Highest cumulative loss occurred with City Compost and glyricidia litter applied. Entisol treatments recorded lower ammonia volatilization compared with Vertisol and Alfisol in all the treatments. Greater volatilization loss of nitrogen in City Compost treatment weas attributable to alkaline pH of the materials itself (pH = 7.6). In the present study, the losses were negligible after 2 weeks. This has led to the inference that decreases in NH4-N level and most probably simultaneous nitrification and denitrificxation reaction.